Comparison performances between MABSA-PI controller and MABSA-PD controller for DC motor position system - Mohamad Harith Hilmi, Fajaffri; Nafrizuan, Mat Yahya (Penerbit UMP, 2023)
The goal of this project is to create two different types of controllers for regulating DC motor position systems which are the MABSA-PI controller and the MABSA-PD controller. The MATLAB controllers are developed using the Simulink toolbox, while the transfer function of a DC motor is obtained from its circuit. Modified adaptive bats sonar algorithm (MABSA) will be implemented in the PI controller and PD controller as the main algorithm. MABSA is one of the swarm intelligences and is usually for an optimization problem. Next, the tuning method for the PI controller and PD controller will be the trial-and-error method. The combination graph of each controller will be shown in Simulink scope as the project is tested for various positions. The controller's ability to regulate the position of a DC motor was studied. The comparision among the system's transient response parameters, including percentage overshoot, rising time (Tr), and settling time (Ts), would be discused. Various toolbox functions available in Simulink software can be employed to repossess these parameter outcomes.